Klausa Relatif Bahasa Karo - Yuanita, Arie (Jurnal Pena Indonesia, 2024)
This research aims to explain the position of core nouns in relative clauses in the Karo language, the types of relative clauses in the Karo language, and strategies for relativizing relative clauses in the Karo language. The research method used in this research to collect data is the library method while analyzing the data using the collection method using techniques for direct elements. From the research results it is shown that the position of the core noun of the Karo language relative clause is classified as a postnominal form, namely the relative clause comes after the core noun. However, apart from being in postnominal form, there are several relative clauses in the Karo language that are also in prenominal form, that is, the relative clause comes before the main noun. There are two types of relative clauses in the Karo language, namely restrictive relative clauses and nonrestrictive clauses. These two types of clauses are quite often found in relative clauses in the Karo language. In connection with the relativity strategy, Karo language clauses apply a permutation strategy. With the permutation strategy, it can be seen that postnominal Karo language relative clauses cannot be expanded because the clauses become ungrammatical, while prenominal Karo language relative clauses can be expanded and are grammatical.